Tracing the Ideological Principles of Al-Qaeda - Seyed Mohammad Hasan Shams (Qom Islamic Azad University, 2019)
Al-Qaeda is a terrorist organization which has a unique interpretation of Islam. This interpretation comes from what is known as the Salafi Movement. According to the Salafi Movement − and the Al Qaeda’s interpretation from Islam − the world is divided into two territories: The Islamic territory and the blasphemous territory. Supposing that it belongs to the Islamic territory, Al-Qaeda believes that it is each Muslim’s duty to declare Jihad against the blasphemous territory so that it can be destroyed. Through their unique interpretation of Islam, the Al-Qaeda’s ultimate objective is to establish an Islamic   caliphate upon an independent territory, propagate the divine laws in their territory, and unite the world’s Muslims for totally annihilating the blasphemous territory. Through analyzing the beliefs and principles of the Salafi Movement, the present study traces the ideological impact of this movement on the establishment of Al-Qaeda. The nature of the study’s methodology is descriptive-analytical, and the library/document survey is its data collection methodology. It becomes evident that in both the Arab and non-Arab worlds, the Al-Qaeda’s cells have directly impacted by the ideological principles of the Salafi Movement, and as a result rendered its radical actions and orientations on the basis of doctrines of this religious ideology.